Transcriptome population genomics reveals severe bottleneck and domestication cost in the African rice (Oryza glaberrima). Issue 9 (18th April 2014) - Nabholz, Benoit; Sarah, Gautier; Sabot, François; Ruiz, Manuel; Adam, Hélène; Nidelet, Sabine; Ghesquière, Alain; Santoni, Sylvain; David, Jacques; Glémin, Sylvain
Abstract The African cultivated rice (Oryza glaberrima) was domesticated in West Africa 3000 years ago. Although less cultivated than the Asian rice (O. sativa), O. glaberrima landraces often display interesting adaptation to rustic environment (e.g. drought). Here, using RNA‐seq technology, we were able to compare more than 12 000 transcripts between 9 O. glaberrima, 10 wild O. barthii and one O. meridionalis individuals. With a synonymous nucleotide diversity πs = 0.0006 per site, O. glaberrima appears as the least genetically diverse crop grass ever documented. Using approximate Bayesian computation, we estimated that O. glaberrima experienced a severe bottleneck during domestication. This demographic scenario almost fully accounts for the pattern of genetic diversity across O. glaberrima genome as we detected very few outliers regions where positive selection may have further impacted genetic diversity. Moreover, the large excess of derived nonsynonymous substitution that we detected suggests that the O. glaberrima population suffered from the 'cost of domestication'. In addition, we used this genome‐scale data set to demonstrate that (i) O. barthii genetic diversity is positively correlated with recombination rate and negatively with gene density, (ii) expression level is negatively correlated with evolutionary constraint, and (iii) one region on chromosome 5 (position 4–6 Mb) exhibits a clear signature of introgression with a yet unidentified Oryza species. This work represents the first genome‐wide survey of the African rice genetic diversity and paves the way for further comparison between the African and the Asian rice, notably regarding the genetics underlying domestication traits.